A discussion of the results of the tests of the Alpha and United States cream separators - Lawry, Walter Fisk (My University, 1900)
Introduction: In the thesis, submitted by Mr. L. W. Waldraven, exhaustive tables are presented of the comparative test of the United States, No. 1, belt-driven cream separator, and the Alpha DeLaval, belt-driven, No. 1. Mr. Waldraven’s thesis also contains notes and full explanations of how the experiments were conducted, power measured and the apparatus used. But it is considered not superfluous to repeat that the greatest care was taken to have the conditions the same for the two machines, even to the same number of drops of oil used, per minute, in each case. In the following graphical representation of the power required by the two separators, the averages of all the tests made on each separator are the results plotted.
Citation: Lawry, Walter Fisk. A discussion of the results of the tests of the Alpha and United States cream separators. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Cream Separator; Equipment; Theses